A tomato and tall fescue intercropping system controls tomato stem rot. Issue 1 (1st January 2019) - Zhou, Yunzhuan; Cen, Huifang; Tian, Danyang; Wang, Chen; Zhang, Yunwei
ABSTRACT: Intercropping can effectively control some plant soil-borne diseases. However, few studies on intercropping have focused on forage grass as companion plants. In this experiment, Festuca arundinacea (tall fescue) was selected as the intercropping forage to explore whether it could control tomato stem rot. We found that: (1) tomato intercropped with tall fescue had a significantly lower disease incidence and disease index of tomato stem rot than sole tomato; (2) the antifungal activities of the root exudates of tomato and tall fescue in intercropping system were significantly higher than those of sole tomato or tall fescue. Meanwhile, it was inferred that the main allelochemicals might be cyclohexane-1, 2-diol and putrescine based on the GC-MS analysis of root exudates of tall fescue. (3) RNA-seq suggested that intercropping with tall fescue significantly upregulated the expression of genes related to pathogenesis-related proteins and hormone metabolism of tomato compared to those in sole tomato.